Design and Development of Solar Powered Automatic Irrigation System for Modernization of Agriculture - Veeramma Yatnalli; Saroja S. Bhusare; B.G. Shivaleelavathi; C. Sheetal; B. Reshma; M. Swetha; H. N. Yashaswini (AGRIVITA, Journal of Agricultural Science, 2023)
The aim of research is to reduce the utilization of water by irrigating the agricultural fields that have low moisture level through the implementation of Wireless Sensor Network (WSN). The ARM-based irrigation solution consists of a Solar Tracking System, Wireless Information Unit (WIU), WSN and Remote Access. The Solar Tracking System utilizes maximum solar energy by using Light Dependent Resistor(LDR) to track the sun. The electric energy produced is stored in the battery which powers the ARM processor. Wireless Information UnitÂ will collect the sensor information from Wireless Sensor Network through the use of Wi-Fi. The system monitors soil-moisture and controls the flow of water using a solenoid valve depending upon the set threshold. In the tank, Ultra Sonic sensor identifies the water level controlled by the WIU.Â An Android application helps the farmer to monitor the water flow and soil moisture remotely. The proposed water management methodologies for agriculture optimizes the water usage and such practices maintain the crop health, keep yield intact, and avoids human intervention. In this proposed system, soil moisture is maintained appropriately to ensure that a good harvest is obtained which in turn preserves different types of nutrients.